Organization of academic language education of future lawyers in the light of Polish-German comparative analyses - Biedroń, Lena (Acta Universitatis Lodziensis. Folia Iuridica, 2018)
The consequence of the European language policy and the implementation of its assumptions is the flow of glottodidactic thought, which encourages reflection on the organization of academic language education in various educational systems. Organization of language education at the law faculties in Poland and Germany is subject to dynamic transformations resulting, inter alia, from the need to adapt foreign language teaching to the requirements of the labour market. The ability to use several foreign languages and knowledge of other legal systems will allow future lawyers to practise in an international environment and is almost a requirement of the modern era, so it is worth considering how to organize the language education process in law faculties, aiming at the professionalization of education.